Gamification strategy to support self-directed learning in a blended learning environment - Palaniappan, Kavitha (2021)
The growth of educational technology has paved ways for educators to integrate newer approach in teaching pedagogy. The shift into blended learning especially in higher education requires learners to be more self-directed. Yet, learners lacking in their self-directed learning lead to a discontinuity of engagement and motivation along the learning process which eventually affects their learning performance, especially among non-major computer science learners learning programming language. Thus, gamification strategy, use of game elements in a nongaming context has been infused into blended learning to support the learners selfdirected learning in a gamified learning environment. This research measures the effect of gamification on learners’ academic performance, investigate their selfdirected learning level within gamification learning environment and identify the relationship between learners self-directed learning level and their gamification learning experience. A pre-experimental research (single group) was carried out for a duration of 5 weeks among a group of 29 learners from a non-major computer science course in UTM undertaking basic programming language subject. The learners SDL and knowledge on the subject was measured with a questionnaire and assessment test before and after the gamification learning intervention. A gamification experience questionnaire was used to evaluate their gamification learning experience after the intervention. The learning environment was infused with gamification in the form of competition to earn points, leaderboard ranks and python programmer badge. 25 learners managed to complete the gamified task successfully and earned the digital badge meanwhile the 4 remaining learners did not manage to complete all the given tasks completely to earn the badge. Top 5 highest rankers were rewarded with prize which has been one of the extrinsic motivation factor on the task completion. The learners academic performance has significantly improved (p=0.000 < 0.05) after the gamification injection from M=15.56 at pre-test to M=19.44 at post-test. Leaners selfdirected learning level increased and there is a significant difference before (M=3.59) and after (M=4.22) the gamification strategy (p=0.000 < 0.05) imposed. Selfmanagement, motivation and self-monitoring were all at high level with significance before and after (p=0.000 < 0.05) the gamified learning activities. The analysis on the relationship between gamification learning experience and self-directed learning showed there is a positive and moderately strong correlation between them (p=0.002, r=0.596) after the intervention and the self-directed learning factors or dimensions are all positively correlated among one another when their relationship was tested. Overall, the learners showed positive outcome in terms of their self-directed learning and gamification experience from the research. The gamification strategy used in the blended learning environment manage to support learner’s self-directed learning.